Communicating facts and ideas in business - Brown, Leland (Prentice-Hall, 1982)
Part I provides the theoretical and conceptual framework necessary for a foundation to understanding the communication processes and for developing the ability to communicate effectively. Part II seeks to help the reader improve his or her written skills; Part III offers suggestions for improving interpersonal and oral communication skills; and the Epilogue looks into the future, exploring job opportunities and the effects of technological innovations on communication.